Mitigation of climate change effects through non-structural flood disaster management in Pekan Town, Malaysia - Mohit, Mohammad Abdul; Sellu, Gajikoh Mohamed (Elsevier, 2013)
Floods bring miseries to the life of thousands of Malaysians every year. Pekan town, located on the banks of the Pahang River, regularly suffers both economic damages and physical destructions caused by the floods. It is anticipated that the climate change effects through a rise in the sea-level, will aggravate both the duration and depth of flooding in the town. This paper studies the flood situation of Pekan town, assesses the intensity of flood damages, anticipates the severity of flooding due to sea-level rise and finally, comes up with the community-based sustainable flood mitigation policies and measures for the town.